AI and nanotechnology integration and future pandemic prediction - Fadilla 'Atyka, Nor Rashid; Marizuana, Mat Daud; Anbia, Adam; Liew, Siaw Hong; Fazlina, Mohd Ali; Nazhatul Hafizah, Kamarudin (Elsevier Inc., 2025)
AI and nanotechnology play crucial roles in combating pandemics like COVID-19. AI aids in screening, tracking, predicting patients, developing medications, and reducing healthcare staff burden. Nanotechnology, through nanomaterials, offers unique properties for preventing, diagnosing, and treating infections like SARS-CoV-2, enhancing pandemic response. There is a need for advanced tools to predict and mitigate the impact of future pandemics as traditional methods often lack the speed and precision required for effective disease surveillance and control. The combination of nanotechnology and AI in healthcare systems presents innovative solutions for societal improvement during pandemics. In this paper, the authors explore the potential of combining these two cutting-edge technologies to enhance early detection, monitoring, and treatment of infectious diseases in providing real-time monitoring and decision support for healthcare professionals. Results from the study demonstrate the potential of the integrated technology to enhance early detection, improve treatment outcomes, and streamline decision-making processes. The integration of nanotechnology and AI in healthcare systems presents innovative solutions for societal improvement before and during a pandemic. These technologies are essential for developing effective strategies to tackle pandemics and improve healthcare systems globally.